The Distinguishing Bacterial Features From Active and Remission Stages of Ulcerative Colitis Revealed by Paired Fecal Metagenomes - Zhu, Ran; Tang, Junrui; Xing, Chengfeng; Nan, Qiong; Liang, Guili; Luo, Juan; Zhou, Jiao; Miao, Yinglei; Cao, Yu; Dai, Shaoxing; Lan, Danfeng (Frontiers in Microbiology, 2022)
Ulcerative colitis (UC) is a serious chronic intestinal inflammatory disease, with an increased incidence in recent years. The intestinal microbiota plays a key role in the pathogenesis of UC. However, there is no unified conclusion on how the intestinal microbiota changes. Most studies focus on the change between UC patients and healthy individuals, rather than the active and remission stage of the same patient. To minimize the influences of genetic differences, environmental and dietary factors, we studied the intestinal microbiota of paired fecal samples from 42 UC patients at the active and remission stages. We identified 175 species of microbes from 11 phyla, and found no difference of the alpha and beta diversities between the active and remission stages. LEfSe and paired t-test analysis revealed differential microbiota at levels of the phyla, class, order, family, genus, and species, including 13 species with differential abundance. For example, CAG-269 sp001916005, Eubacterium F sp003491505, Lachnospira sp000436475, et al. were down-regulated in the remission, while the species of Parabacteroides distasonis, Prevotellamassilia sp900540885, CAG-495 sp001917125, et al. were up-regulated in the remission. The 13 species can effectively distinguish the active and remission stages. Functional analysis showed that the sporulation and biosynthesis were down-regulated in remission of UC. Our study suggests that the 13 species together may serve as a biomarker panel for diagnosing the active and remission UC, which provides a valuable reference for the treatment of UC patients by FMT or other therapeutic methods.